Development and Validation of a Daily Habit Scale - Georgiev, Dejan; Christie, Rosie; Torkamani, Mariam; Song, Ruifeng; Limousin, Patricia; Jahanshahi, Marjan (Frontiers in Neuroscience, 2022)
Habits are defined as automatic behaviours triggered by cues and performed without awareness. They are difficult to control and mentally efficient, which contrasts with goal-directed behaviour, which is characterised by active thought, high computational effort, and the ability to modify this behaviour in response to a changing environment and contextual demands. Habits are not only defined by the frequency with which a behaviour is performed but represent a complex construct that also includes the strength and automaticity of the habitual behaviour. We report here the development and validation of a Daily Habit Scale (DHS) to assess the frequency, automaticity, and strength of daily habits in healthy individuals. Item reduction based on factor analysis resulted in a scale with 38 items grouped into eight factors explaining 52.91% of the variance. The DHS showed very good internal consistency (Cronbach alpha=0.738) and test-retest reliability (Intraclass correlation coefficient=0.892, p<0.001) as well as convergent and divergent reliability compared to other scales measuring habits. We found a significant effect of age, gender, anxiety, and depression on the DHS. Considering certain limitations of the DHS, such as not considering the context of performance of habits, and the absence of certain items, such as transportation use, the results of this study suggest that DHS is a reliable and valid measure of daily habits that can be used by both clinicians and researchers as a measure of daily habits.